A single session of a beach volleyball exergame did not improve state anxiety level in healthy adult women - Vinnycius Nunes de Oliveira; Ricardo Borges Viana; João Victor Rosa de Freitas; Mila Alves Matos Rodrigues; Marilia Santos Andrade; Rodrigo Luiz Vancini; Katja Weiss; Beat Knechtle; Claudio Andre Barbosa de Lira (BMC, 2024)
Abstract This study evaluated the acute effect of the exergame Kinect Sports® beach volleyball on state anxiety level in adult women. Thirty healthy adult women (age: 21 [4] years, body mass: 54.70 [19.50] kg, height: 1.61 ± 0.05 m, and body mass index: 21.87 [5.76] kg/m2, data are expressed as median [interquartile range] and as the mean ± standard deviation) were assigned to play an exergame of beach volleyball in singleplayer mode session (intervention session) for ~ 30 min using the Xbox 360 Kinect® or remained seated (control session). State anxiety was evaluated before and after the intervention and control sessions through the State-Trait Anxiety Inventory. State anxiety obtained in both sessions (exergame and control) was classified as intermediate before (median: 36.00 [IQR: 4.75] and mean = 38.73 ± 7.23, respectively) and after (mean: 34.86 ± 6.81 and mean: 37.66 ± 8.44, respectively). Friedman test found no time significant effect on state anxiety of the sessions (χ2 [3] = 6.45, p-value = 0.092, Kendall's W = 0.07 "trivial"). In conclusion, the present study showed that there were no significant differences in the state anxiety level after an acute session of the exergame beach volleyball.